The Relationship Between Architecture and Urban Residents' Mental Health - Nasiri Behrooz (اکولوژی انسانی)
Urban architecture, as a key element in the design of living spaces, has a profound impact on the mental health of residents. Urban spaces, with their specific characteristics, can lead to feelings of calm or anxiety in individuals. Factors that can influence mental health include natural light, access to green spaces, the design of public areas, as well as noise quality and air pollution. For instance, green spaces and parks not only provide opportunities for recreation and physical activities, but they also help reduce stress and anxiety. Studies have shown that living near green spaces can improve mood and reduce symptoms of depression. Moreover, architecturally designed spaces that facilitate social interaction can strengthen social relationships and foster a sense of belonging to the community, which are key factors in mental health. Additionally, urban space design should consider the psychological needs of residents. Crowded and chaotic spaces can create feelings of restlessness and insecurity, while orderly and calm spaces can enhance feelings of comfort and safety. For example, wide streets with shaded trees and appropriate lighting can create a pleasant and relaxing environment for walking and leisure. Furthermore, the presence of amenities such as cafes and restaurants in public spaces can contribute to the creation of focal points and social interactions. Ultimately, attention to human-centered design principles and the psychological needs of residents in urban architecture can lead to an improvement in their quality of life and mental health. Therefore, architects and urban planners should seriously consider this issue and strive to create spaces that are not only beautiful and attractive but also have a positive impact on residents' mental health.